Unemployment in Germany and the eurosclerosis debate: Can the Hartz Reforms induce higher employment? - Denis Drechsler (Universität Potsdam, Lehrstuhl Finanzwissenschaft, 2005)
Many European countries have experienced a significant increase of unemployment in recent years. This paper reviews several theoretical models that try to explain this phenomenon. Predominantly, these models claim a link between the poor performance of European labor markets and the high level of market regulation. Commonly referred to as the Eurosclerosis debate, prominent approaches consider insider-outsider relationships, search-models, and the influence of hiring and firing costs on equilibrium employment. The paper presents empirical evidence of each model and studies the relevance of the identified rigidities as a determinant of high unemployment in Europe. Furthermore, a case study analyzes the unemployment problem in Germany and critically discusses new reform efforts. In particular this section analyzes whether the recently enacted Hartz reforms can induce higher employment.
urn:nbn:de:kobv:517-opus-9036
Keywords: 330; Arbeitslosigkeit; Arbeitsmarktpolitik; Reform; Wirkungsanalyse; Beschäftigungseffekt; Arbeitsmarktflexibilisierung; Deutschland